Conceptual Approach to Innovation - a Modern Tool to Enhance Entrepreneurial Competitiveness - Elena SIMCIUC; Cristina COŞCIUG (Eastern European Journal of Regional Studies, 2017)
The paper studies the evolution of the innovation process generations, analyzes the meaning of the innovation concept and its influence on the performance of the economic agents. The issue addressed: the lack of a harmonized and unanimously accepted terminology of the term „innovation” leads to permanent discussions on this subject and to the impossibility of developing the harmonized methodology of its evaluation. Research methods: observation, analysis of documents, scientific papers and works. Conclusion: A significant number of studies have examined the impact of different forms of innovation and its effects on business performance, the findings indicating expressly that innovation, in its various forms and aspects, was the strongest predictor of business performance.